TEATER SEBAGAI WACANA: SEBUAH METODE DALAM GARAPAN SENI PERTUNJUKAN PADEPOKAN SENI BAGONG KUSSUDIARDJA (PSBK) - Satrya HD, Dharma (TAMUMATRA, 2018)
This study focuses on theatre theory art resident (PSBK) developed by Bagong Kussudiarda. It applied ethnography research. Researchers is as the audience as well as Brigade Pamungkas Jagongan Wagen (JW) team. This research is about the creative process from the researcher?s experience. Researchers conducted observations actively in his creative process, so this research is an ethnographic writing about PSBK theatre process. The result shows that theatre is stated as a method of early theatre production.  Discourses of theatre are viewed genealogically, from Teater Menyenangkan, Teater Super Menyenangkan, Sandiwara Teater Perempuan, Adi Seni Teater, Sekar Sajen, Jenaka Akting Teater, and Mendadak Teatrik Intrik Musik Asik. PSBK considers theatre not only as the subject, but also as the object of performance art. Keywords: PSBK, theatre method, discourse